The COVID-19 Pandemic Impact on the Outcome of Medically Assisted Reproduction Pregnancies - Huri, Mor; Noferi, Virginia; Renda, Irene; Piazzini, Francesca; Benemei, Silvia; Coccia, Maria Elisabetta (Frontiers in Reproductive Health, 2022)
Background The impact of the Coronavirus Disease-2019 (COVID-19) pandemic on pregnancy is not well-understood. During the outbreak, the initial approach suggested by the major societies was to postpone all non-urgent assisted reproductive technology (ART) treatments. Nevertheless, the Italian Society of Fertility and Sterility and Reproductive Medicine considered ethically correct to proceed with ART treatments, as the infertility rate is increasing over time, with a consistent decline in the live birth rate. The objective of our study was to assess the impact of the COVID-19 pandemic on the outcomes of ART pregnancies, in terms of early pregnancy loss, overall success rate, and live birth rate. Methods We conducted a single-center retro-prospective cohort study. Patients who underwent ART treatments from 1 March 2020 to 28 February 2021 (pandemic ART cohort, pART; n = 749) and from 1 March 2019 to 29 February 2020 (control cohort, CTR; n = 844) were enrolled. The study had a duration of 24 months. Patients underwent baseline severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) nasopharyngeal swab; quantitative serum beta human chorionic gonadotropin (β-hCG) to assess pregnancy; pelvic transvaginal ultrasound; and follow-up until delivery. The study took place at the ART Center of the University Hospital in Florence, Italy. Results There were not statistically significant differences on implantation rate (pART 0.348 ± 0.034 vs. CTR 0.365 ± 0.033, CI = 95%, p = 0.49), clinical pregnancy rate (pART 0.847 ± 0.044 vs. CTR 0.864 ± 0.038, CI = 95%, p = 0.56), and ectopic pregnancy rate (pART 0.008 ± 0.011 vs. CTR 0.01 ± 0.011, CI = 95%, p = 0.79). Neither first trimester miscarriage rate was different between the groups (pART 0.224 ± 0.056 vs. CTR 0.213 ± 0.05, CI = 95%, p = 0.77) nor second trimester miscarriage rate (pART 0.018 ± 0.018 vs. CTR 0.019 ± 0.017, CI = 95%, p = 0.95). Live birth rate remained unchanged during the pandemic (pART 0.22 ± 0.03 vs. CTR 0.239 ± 0.029, CI = 95%, p = 0.37) and stable even when compared to our center rate between 2015 and 2019 (pART 0.222 ± 0.03 vs. general rate 0.224 ± 0.014, CI = 95%, p = 0.83). Conclusion The COVID-19 pandemic did not cause a statistically significant change in the live birth rate and in the pregnancy loss rate. ART during the COVID-19 pandemic can be considered fair and safe, ethically and medically appropriate. Patients and physicians should be reassured that ART pregnancy outcomes do not seem to be jeopardized by the pandemic state.